"Tao follows its own way" and tourists' behaviour ecologicalisation: philosophical enlightenment from Chinese Taoism. (1st January 2013) - Zeng, Wujia; Cheng, Li; Ouyang, Liqun
As a new tourism mode, ecotourism has been widely practiced and researched. However, in practice, it is difficult for ecotourists to realise their original intention and promote sustainable development of the scenery in strict accordance with their fundamental principles and ways. This paper argues that the key cause of this phenomenon is that the value of tourists' behaviour has not completely become ecological. The Taoists who pursue joining Tao shall inevitably perform the ideal ecotourism behaviour. In attempting to incorporate some concepts of Taoism, which developed in China and has a long history of traditional religion, the paper points out that the Taoist thoughts on values and practices arising from "Tao follows its own way" provide a possible conscious approach to the strict ecological transformation of tourists' behaviour and also offer a new philosophical view for ecotourism development.